2014
DOI: 10.1103/physrevb.89.184407
|View full text |Cite
|
Sign up to set email alerts
|

Quantums=12antiferromagnets on Archimedean lattices: The route from semiclassical magnetic order to nonmagnetic quantum states

Abstract: We investigate ground states of s=1/2 Heisenberg antiferromagnets on the eleven twodimensional (2D) Archimedian lattices by using the coupled cluster method. Magnetic interactions and quantum fluctuations play against each other subtly in 2D quantum magnets and the magnetic ordering is thus sensitive to the features of lattice topology. Archimedean lattices are those lattices that have 2D arrangements of regular polygons and they often build the underlying magnetic lattices of insulating quasi-two-dimensional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 67 publications
(98 reference statements)
1
98
0
Order By: Relevance
“…Firstly, the method has now been used in well over 100 different papers for a wide variety of frustrated quantum magnets (and see, e.g., Refs. [15,41,[54][55][56] and references cited therein), where the same extrapolation schemes as used here have been utilized, and in virtually all of which the results obtained have been shown to be either the best, or among the best, available. Secondly, in all of the many cases in the literature cited, where it has been possible to compare results obtained from different LSUBn input sets, it has been shown that the obtained extrapolants for all physical parameters agree with one another, typically to ∼ 1% or better.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, the method has now been used in well over 100 different papers for a wide variety of frustrated quantum magnets (and see, e.g., Refs. [15,41,[54][55][56] and references cited therein), where the same extrapolation schemes as used here have been utilized, and in virtually all of which the results obtained have been shown to be either the best, or among the best, available. Secondly, in all of the many cases in the literature cited, where it has been possible to compare results obtained from different LSUBn input sets, it has been shown that the obtained extrapolants for all physical parameters agree with one another, typically to ∼ 1% or better.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…For both the GS and ES calculations we employ the well-known lattice animalbased subsystem (LSUBn) truncation hierarchy, which has been much studied and utilized for a wide variety of spin-lattice problems in the past (and see e.g., Refs. [15,41,54,56,68,69,93] and references cited therein).…”
Section: The Coupled Cluster Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This happened partly due to the rise of the geometrically-frustrated AFMs on non-bipartite Archimedean lattices [Diep, 2004, Farnell et al, 2014, Lacroix et al, 2011, Lhuillier, 2005, Lhuillier and Misguich, 2001, Sachdev, 2011, Schollwöck et al, 2004 (geometrical frustration is a type of frustration where the competition between Hamiltonian terms comes from the arrangement of spins on non-trivial lattice plaquettes -see below). Interestingly, the existence of geometrical frustration is enough by itself to often lead to the 'melting' of the magnetic ordering, stabilizing a family of nonmagnetic phases, collectively classified as spin liquids (also known as paramagnetic states [Balents, 2010, Chen et al, 2010, Kalmeyer and Laughlin, 1987, Read and Sachdev, 1991, Wen, 1991, Wen et al, 1989, Wen, 2002; spin glasses [Diep, 2004, Lacroix et al, 2011, Sachdev, 2011 form the other type of quantum states with vanishing average magnetization that are essentially stabilized due to the frustration, however, are not considered in this thesis).…”
Section: (B) It Is Widely Believed That the Celebratedmentioning
confidence: 99%